Practical Methods to Improve Client Compliance in General Medicine - Jose Luis Turabian (International Journal of General Practice, 2020)
There is a gap between theoretical knowledge about strategies and the techniques or methods to apply in the practice of the consultation to improve compliance. Within the framework of these strategies, a number of techniques to be used in certain situations can be cited: 1) Assessing readiness to change, importance and confidence; 2) Instruments for decision support; 3) Technique of the
Keywords: Physician-Patient Communication